1975
DOI: 10.1017/s002211207500208x
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Doppler anemometer measurements in drag-reducing channel flows

Abstract: The objective of this study was to make velocity measurements in drag-reducing flows which would be sufficient in scope and accuracy to test proposed models of drag-reducing flows and to yield new information about the mechanisms of drag reduction. Consequently, measurements of the mean and turbulence intensity of the streamwise velocity component were made in fully developed, turbulent, drag-reducing flow in a two-dimensional channel with a laser-Doppler anemometer. The anemometer was operated in the individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(35 citation statements)
references
References 21 publications
(11 reference statements)
7
27
0
Order By: Relevance
“…28,29 The equations of mean velocity distribution has been applied to the viscoelastic flows; it is found that the equations derived are in good agreement with experimental data measured by Virk, [30][31][32] Seyer and Metzner, 33 James and Acosta, 34 Reischman and Tiederman, 14 Rudd,13 etc.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…28,29 The equations of mean velocity distribution has been applied to the viscoelastic flows; it is found that the equations derived are in good agreement with experimental data measured by Virk, [30][31][32] Seyer and Metzner, 33 James and Acosta, 34 Reischman and Tiederman, 14 Rudd,13 etc.…”
Section: Introductionmentioning
confidence: 74%
“…Early LDV measurement in polymer drag-reducing flows was reported by Rudd, 13 then followed by Reischman and Tiederman, 14 Berner and Scrivener, 15 Berman, 16 etc. The velocity fluctuations and energy spectrum in streamwise direction were observed and reported by them; one of the important discoveries was that the root mean square of streamwise velocity in drag-reducing flows is slightly higher than that in Newtonian fluid flows, and the energy is redistributed from high frequencies to low frequencies.…”
Section: Introductionmentioning
confidence: 97%
“…They found that there was an asymptotic value for the maximum drag reduction, which is independent of polymers and pipe diameter. The phenomenon in the regions where drag reduction occurs with polymer additives were also discussed by Lumley [3] and Reischman and Tiederman [4] who presented experimental evidences that the buffer region changed and played an important role in drag-reducing flows. Measurements in chan-nel flow with polymer injection, using two-component laserDoppler velocimetry (LDV) were performed by Luchik and Tiederman [5] and Walker and Tiederman [6].…”
Section: Introductionmentioning
confidence: 81%
“…This is a variation of the 5-10 p.m seed used previously (12,16,17). The upper limit of 10 p.m diameter was maintained so that all of the particles were capable of accurately following the flow.…”
Section: Aciqĩ~wledgementsmentioning
confidence: 99%
“…The acrylic , two-dimensional channel was 72 inches long , 12 inches high and approximatel y one inch wide (17). A section containing b a f f l e plates and screens was added at the downstream end of the channe l (16) Notice that all of the make-up water is f i l t e r e d .…”
Section: Experimental Apparatu Smentioning
confidence: 99%